The Additionality Impact of a Matching Grant Program for Small Firms : Experimental Evidence from Yemen - Mckenzie, David (World Bank, Washington, DC, 2015)
Matching grants are one of the most common types of private sector development programs used in developing countries. But government subsidies to private firms can be controversial. A key question is that of additionality: do these programs get firms to undertake innovative activities that they would not otherwise do, or merely subsidize activities that would take place anyway? Randomized controlled trials can provide the counterfactual needed to answer this question, but efforts to experiment with matching grant programs have often failed. This paper uses a randomized controlled trial of a matching grant program for firms in the Republic of Yemen to demonstrate the feasibility of conducting experiments with well-designed programs, and to measure the additionality impact. In the first year, the matching grant is found to have led to more product innovation, firms upgrading their accounting systems, marketing more, making more capital investments, and being more likely to report their sales grew.